Biomecânica da união dente-implante com plataforma restauradora reduzida, sistema de retenção tipo cone morse e roscas quadradas: uma análise por elementos finitos - Adriana Vieira Martins (2016)
The goal of this study was to evaluate, from the Finite Element Method, the biomechanics of implant-tooth union and implant-implant and to establish a qualitative analysis with previous photoelastic findings. Four three-dimensional models were planned: two Test Models (teeth attached to implants) and two Control Models (the same condition, however implant supported). The implants (ANKYLOS® - Dentsply) showed conical connection, square threads and Switching pillars. Their dimensions, external angles and abutments were obtained from a profile projector. Already, teeth and dentures, from direct view, had their external forms built in CAD platform (SOLIDSWORKS). Alveolar support wasconfigured as a rectangle (68/30/15 mm). All the pillars were placed in the alveolar support, as the pre-existing physical models, generating solid models. The periodontal ligament consists of a layer of 0.25 mm thick in polyether (Impregum Soft, 3M Espe). The models of teeth trumped up of dentin, abutments and implants of pure titanium, prosthetics of Nickel-Chrome (Ni-Cr) alloy and alveolar support in photoelastic resin (Araldite® - Chemicals Ciba S/A of Brazil). The resin properties were obtained by traction tests. Punctual and vertical static load of 150 N was applied. The results of these tests showed lower concentration of tension in the cervical aspect of the test group implants. When comparing these findings with the photoelastic previously found, it was possible to establish a direct relation between the areas most requested for fixed prosthesis (FP) models of three elements. It was concluded that, for the studied conditions tapered connection, square threads and Platform Switching restoration , joining teeth implants seems to be a viable clinical therapy, suggesting, inclusive, to be more favorable than to join implants each other. Moreover, from the positive affinity between the findings of the two techniques, it was possible to consider validated the mathematical models of fixed prosthesis of three elements.